Plan de negocios para el lanzamiento de un nuevo fertilizante para cultivos de soya - Jiménez Balón, Ingrid (2009)
The agroindustrial sector is one of the most important sectors of the economy. This is due in great measure to the strengths that Ecuador has to foment its development. Inside the agricultural sector, the cultivation of the soybean is one of the main sources of wealth for several countries on a world level, and it is an activity with aims of great economic growth for the diversity of uses that it possesses, as much for the human consumption as animal. The soybean is one of the most extractive cultivations of nutrients and paradoxically one of the fewer fertilized in the country. The proposal of this project is to carry out a plan of business to present to the market a new specialized fertilizer for cultivation of the soybean that allows the farmer and/or producer to obtain high production levels. For effects of the study, marketing strategies are included that allow Fertisa to position the new product to optimize their utilities in the long term; of communication with the purpose to make the product stand out and to persuade its consumption through advertising means; and of financial to evaluate the viability of the project.